Tajul Muluk: A Traditional Malay Text of Ethnobotany and Ethnomedicine - MOHD AFFENDI MOHD SHAFRI; AIN NAJIHAH NAZARUDIN (Borneo Journal of Resource Science and Technology, 2022)
Ethnobotanical and ethnomedical knowledge of the Malays could be known either through oral sources or documented sources. The traditional sources of Malay medicine are useful for traditional and modern pharmaceuticals development in Malaysia and for conservation of biodiversity. This study aims to extract and categorise the ethnobotanical and ethnomedical contents documented in the medical chapter of Tajul Muluk, in the Malay ancient text. Transliteration and data extraction were carried out in order to identify and classify the information in the text. The manuscript has 292 medical interventions for 56 different diseases such as cough, fever, and mental health issues. There are descriptions available for different medical formulations using 209 plant-based materials, 12 animal-based materials and 40 other types. Many of the name and use of the materials are now rare or not well-known in modern today’s society. Medical descriptions listed in Tajul Muluk will be a documented proof of herbs used by local Malay population utilised as ethnobotanical and ethnomedical resources. Hence retrieving useful ancient documental knowledge should be explored in finding useful cures and alternatives therapeutics for various diseases.